PHYSICAL QUALITY OF SOYBEAN GRAINS, CULTIVAR TMG115RR, SUBMITTED TO SIMULATION OF RAIN DURING THE DELAY OF HARVEST - ANDRADE, Patrícia de Jesus; FERRONATO, Alessandro; CAMPELO JUNIOR, José Holanda; CANEPPELE5, Maria Aparecida Braga (Scientia Agraria, 2010)
The occurrence of rain can reduce the quality of grain, because of the successive retractions and swelling, as the harvest is delayed. The objective of this research was evaluating physical quality of the soy grains, cultivar TMG115RR, submitted to four times of simulation of rain (control treatment, one, two and three hours) and harvest at stadium R9 and after five, 10, 15 and 22 days in October 2007 and stadium R9 and after five, 10 and 15 for April 2008, in the experimental field at the University of Várzea Grande-MT. In October 2007, with 5 days simulation of rain the total of damaged grains exceeded the limit of tolerance provided in brazilian legislation. At 10 days of harvested retardation the percentage of grains moldy exceeded four times the limit of tolerance for marketing for the industry or other purposes. In cropping seasons of April 2008 the percentage of water content of grain, the second harvest, was higher than recommended for the maintenance of their quality, which is 14%. The defect of higher occurrence in the two years was moldy grains. The control treatment showed percentages of damaged grain more than 8%. At the end of 15 days to delay the harvest, more than 50% of grains were damaged. The delay of harvest associated with the end of harvest rains cause the deterioration of grain.